Synthesis and optimization for rotor profiles in twin rotor screw compressors - Su, SH; Tseng, CH (My University, 2000)
This paper proposes a systematic synthesis method for twin-screw rotor profiles for compressors. Both ''original generating curves'' and "generated curves" are distributed on each rotor profile, and all the geometric parameters of these curves can be determined with satisfying the conditions of continuity in tangency by given only several specific parameter values. The contact lines on rotor surfaces and the blowhole area calculation are also presented Three cases of optimization problems are shown in this paper and both contact-line length and blowhole area are reduced when letting the contact-line length be the object function with a constraint of blowhole area.